Miocardite Lúpica: a propósito de um caso clínico - Costa, S (2005)
Myocarditis is one of the many possible forms of cardiac involvement in systemic lupus erythematosus. Its clinical presentation ranges from asymptomatic patients with self-limited disease to fulminant heart failure that can lead to death. In most cases treatment consists of supportive care only. The authors present the case of a patient with lupus myocarditis.